Fracture Neck Of Femur - A Local Experience - Lik Han, Ong; Sabaruddin, Abdullah; Ankimtay, Rutel; Faris, Kamaruddin (MALAYSIAN ORTHOPAEDIC ASSOCIATION, 2018)
Hip fractures is one of the commonest in elderly patients with various co-morbidities. The incidence of hip fracture in Malaysia is about 90/100 000 population and commoner in women.1 Mortality rate within six months after femoral neck fracture is reported at about 11-23% and 22-29% at one-year worldwide. Therefore, we evaluate all the neck of femur fracture patients who were admitted for surgery to create a greater understanding of peri-operative risk and possible correlation to post-operative prognosis.